Motor unit activation and force production during eccentric, concentric and isometric actions - Linnamo, V. (Studies in Sport, Physical Education and Health, 2002)
The aim of the present series of studies was to examine force and myoelectrical activity in human forearm flexors and knee extensors during dynamic andisometric muscle actions. The main purposes were 1) to clarify the methodological issues regarding the measurements of maximal force, EMG and EMG power spectrum in eccentric, concentric and isometric conditions, 2) to examine the motor unit activation patterns during dynamic and isometric actions by following the behavior of the EMG power spectrum and by utilizing selective intramuscular fine wire electrodes, and 3) to examine the effects of fatigue on force production, aEMG and EMG power spectrum in eccentric and concentric actions. The results showed that eccentric force measured after the onset of the stretch is higher than the isometric preactivation force preceding the movement regardless of the stretching velocity or of the joint angle. However, due to possible inhibition during maximal eccentric action the maximal eccentric force measured in the middle part of the movement may in some situations be exceeded by separately measured isometric force. Lower median frequency (MF) during eccentric than in concentric actions would not support the concept that fast motor units would be selectively recruited during eccentric action. In concentric actions MF increased with increased movement velocity which could indicate increased activation of fast motor units. A more detailed examination of MF showed, however, that window placement of Fast Fourier Transformation (FFT) and the part of the signal chosen for the analysis may be of crucial importance. Intramuscular spike-amplitude frequency (ISAF) analysis suggests that in eccentric actions with isometric preactivation all motor units may become recruited at lower relative force level than in isometric and in concentric actions and the additional force is achieved by increased firing rate of the active units. Despite possible inhibition in eccentric actions the relative force decrease after fatiguing maximal eccentric and concentric exercise can be similar after both exercise types provided that the movement is always started with maximal isometric preactivation.